Inter-limb asymmetries in professional male basketball and volleyball players: bilateral vs. unilateral jump comparison - Cabarkapa, D.; Cabarkapa, D. V.; Fry, A. C. (International Biomechanics, 2025)
The purpose of the present study was to examine differences in inter-limb asymmetries between countermovement vertical jump (CMJ) and single-leg jump (SLJ) performed on an innovative portable force plate system. Seventy professional athletes competing in top-tier international leagues (e.g. NBA, Super League) participated in this investigation. Following the completion of a standardized warm-up, athletes stepped on a uni-axial dual-force plate system and performed three CMJs and six SLJs without an arm swing in randomized order. Peak takeoff and landing forces were recorded for each limb, from which asymmetry percentages were derived. Wilcoxon signed-rank test was used to make statistical comparisons (p < 0.05). Significant differences were found in all asymmetry-related metrics, overall (CMJ vs. SLJ; takeoff: 7.2 vs. 1.0%; landing: 3.3 vs. 6.8%) and within each sport. Peak takeoff force asymmetry was considerably greater in CMJ than in SLJ, while peak landing force asymmetry displayed a reverse trend, with notably greater inter-limb asymmetries being detected within SLJ than CMJ. While both tests can offer useful information to sports practitioners, these results suggest that CMJ and SLJ should not be used interchangeably but rather in conjunction with one another to obtain a better insight into athletes` performance capabilities and inter-limb asymmetry magnitudes.